Ultra high pressure metamorphism in felsic rocks: the garnet – phengite gneisses and quartzites from Lanterman Range (Antarctica) - PALMERI, R.; GHIRIBELLI, B.; TALARICO, F. M.; RICCI, C. A. (European Journal of Mineralogy, 2003)
Mesostructural and microstructural relations between eclogitic boudins and country gneisses in the Ross Orogen of the Lanterman Range (Northern Victoria Land, Antarctica) are in some areas characterized by interlayering with sharp contacts on a cm scale, which indicate that the two rock-types underwent a common metamorphic evolution. Contrary to many other UHP felsic rocks that only preserve a poor record of the HP stage, the studied rocks have recorded a metamorphic history ranging from initial prograde amphibolite facies through the eclogite facies to the retrogressive amphibolite facies. The prograde amphibolite stage is documented by garnet relics preserving prograde zoning and bearing biotite, plagioclase, muscovite, phengite and rutile inclusions. The eclogite stage is characterized by the coexistence of phengite with pyrope-grossularite rich garnet, the latter containing phengite and paragonite inclusions, and by radial fractures within garnet around quartz pseudomorphs after coesite. Symplectites have formed during the amphibolite-facies retrogression. They consist mainly of biotite + plagioclase around phengite and garnet; muscovite, biotite and plagioclase grew along the main foliation. The reconstructed metamorphic evolution, involves a steep prograde and retrograde PT path as well as a HP-T peak. Along with the geochronological evidence of fast exhumation, this supports a model of arc-continent collision, with the HP rocks belonging to the over-riding plate. Their exhumation is mainly controlled by extension related to renewed "rollback" of subduction in front of the orogenic zone.